Code of medical ethics in Islam: a case study of the code of Medical Ethics of the Malaysian Medical Association (MMA) - Amanullah, Muhammad (Intellectbase International Consortium, 2012)
In order to perform duties excellently and deliver services to others efficiently and ethically, and to avoid inflicting of harms to them, specialists, employers, employees and workers of every profession must follow certain ethics. The profession of medical doctors is not an exception. Sometimes non-compliance of medical doctors with ethics causes severe harms to their patients. Islam prescribes sets of ethics for all professions including the profession of medical doctors. Analyzing relevant verses of the Qur’an and ahadith of the Prophet (p. b. u. h.), this paper intends to discuss the code of medical ethics in Islam. Likewise, it aims to evaluate the code of medical ethics of the Malaysian Medical Association (MMA) in light of the code of medical ethics in Islam. Finally, it strives to provide some suggestions to improve the code of medical ethics of MMA. This paper may conclude that Islam has a comprehensive code of medical ethics; and in order to make a comprehensive code of medical ethics, the code of medical ethics of MMA requires some improvement and modification.